Environmental Performance Analysis Of CV Barokah Tofu Waste Factory Using Green Productivity - Rachmad Hidayat; Nuriyanti Arifiyah; Rayhan Ahsanul Hidayat (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Tofu is a food product that is a necessity for daily consumption by the community. The basic ingredient in making tofu is soybeans which have high nutritional value and can be a healthy protein alternative for the community. Tofu is made from coagulated soybean seed sediment, so that the processing produces water which becomes waste in the tofu-making industry. In increasing production it is necessary to have attention to environmental performance. The aspect of environmental performance is in the form of liquid waste resulting from a large number of tofu production processes. The purpose of this study is to analyze the liquid waste from tofu production using the Green Productivity (GP) method to provide suggestions for improvements in increasing company productivity. Based on the results of the study, the company has an initial environmental performance index (EPI) of -376.305. The initial Green Productivity Index (GPI) at CV Barokah has a value of 0.003 and GPI Liquid Waste of 0.75. There are two alternative solutions, namely the utilization of liquid waste to become Nata de soya and liquid organic fertilizer. The alternative chosen is the utilization of liquid waste as organic fertilizer with a profit of Rp. 126,447,163 with the final productivity value also increasing to 703.10%.